Pengaruh Partisipasi Orang Tua Dalam Pendidikan Anak Usia Dini Terhadap Pencapaian Akademik Anak - Rachma, Siti Ainnur; Yunika, Fisi Dwi; Larasati; Damayanti, Aprilia Nurri; Mochamad Ganiadi (SEUNEUBOK LADA: Jurnal ilmu-ilmu Sejarah, Sosial, Budaya dan Pendidikan, 2025)
A key component in improving education standards is parental involvement. Inequality of treatment between parents and teachers results from parents' ignorance of how young children learn, which can stunt children's growth and make them feel insecure. This study discusses the effect of parental participation in early childhood education on children's academic achievement. Parental involvement is an important factor that can support children's development, especially in terms of learning achievement. This study explains how parents play an active role through learning assistance at home, communication with teachers, and involvement in school activities. This involvement not only helps children understand the subject matter, but also plays a role in shaping children's character, discipline and self-con. This research highlights the importance of synergy between parents and schools in creating a conducive learning environment for early childhood. The results of the study are expected to be taken into consideration for educators and parents in improving the quality of early childhood education so that children's learning achievement can be optimal. This research uses a qualitative method with a literature study approach. The results obtained show that: 1) High parental participation has a positive effect on children's academic achievement, especially in improving reading, counting and social skills; 2) Factors that influence the level of parental participation include awareness of the importance of education, available time, and socioeconomic and cultural factors.